The medial frontal cortex contributes to but does not organize rat exploratory behavior. (12th November 2016) - Blankenship, Philip A.; Stuebing, Sarah L.; Winter, Shawn S.; Cheatwood, Joseph L.; Benson, James D.; Whishaw, Ian Q.; Wallace, Douglas G.
Highlights: Rats use self-movement cues to organize their exploratory behavior. Medial frontal lesions disrupt exploratory behavior under light and dark conditions. Behavioral disruptions are consistent with impaired motor coordination. Behavioral disruptions are consistent with impaired egocentric processing. Medial frontal cortex is required, but not sufficient for idiothetic cue processing. Abstract: Animals use multiple strategies to maintain spatial orientation. Dead reckoning is a form of spatial navigation that depends on self-movement cue processing. During dead reckoning, the generation of self-movement cues from a starting position to an animal's current position allow for the estimation of direction and distance to the position movement originated. A network of brain structures has been implicated in dead reckoning. Recent work has provided evidence that the medial frontal cortex may contribute to dead reckoning in this network of brain structures. The current study investigated the organization of rat exploratory behavior subsequent to medial frontal cortex aspiration lesions under light and dark conditions. Disruptions in exploratory behavior associated with medial frontal lesions were consistent with impaired motor coordination, response inhibition, or egocentric reference frame. These processes are necessary for spatial orientation; however, they are not sufficient for self-movement cue processing. Therefore it is possible that the medial frontal cortex provides processing resources that support dead reckoning in other brain structures but does not of itself compute the kinematic details of dead reckoning.